PENGARUH KUALITAS KINERJA TERHADAP KEPUASAN PESERTA PADA KEGIATAN PERJALANAN INSENTIF BANK PERMATA KE EROPA - Fetty Nurmala Rossi (Journal of Tourism Destination and Attraction, 2019)
This article explore the relationship between quality of performance towards satisfaction in Incentive Travel context. The research concluded that incentive travel in Europe has overall satisfaction of to attendees. Respondents were attendees who get reward from their company (Permata Bank). This study also conducted to measure of whether quality performance sub variable also affect to satisfaction. The aim is see how much attendees get the satisfaction from each sub variable. From the research finding revealed that of the four sub variables of performance quality, generic features and comfort amenities had the most influencing on determining satisfaction.